Perspectives on RNA Vaccine Candidates for COVID-19 - Borah, Pobitra; Deb, Pran Kishore; Al-Shar’i, Nizar A.; Dahabiyeh, Lina A.; Venugopala, Katharigatta N.; Singh, Vinayak; Shinu, Pottathil; Hussain, Snawar; Deka, Satyendra; Chandrasekaran, Balakumar; Jaradat, Da’san M. M. (Frontiers in Molecular Biosciences, 2021)
With the current outbreak caused by SARS-CoV-2, vaccination is acclaimed as a public health priority. Rapid genetic sequencing of SARS-CoV-2 has triggered the scientific community to search for effective vaccines. Collaborative approaches from research institutes and biotech companies have acknowledged the use of viral proteins as potential vaccine candidates against COVID-19. Nucleic acid (DNA or RNA) vaccines are considered the next generation vaccines as they can be rapidly designed to encode any desirable viral sequence including the highly conserved antigen sequences. RNA vaccines being less prone to host genome integration (cons of DNA vaccines) and anti-vector immunity (a compromising factor of viral vectors) offer a great potential as a front-runner for universal COVID-19 vaccine. The proof of concept for RNA-based vaccines has already been proven in humans, and the prospects for commercialization are very encouraging as well. With the emergence of COVID-19, mRNA-1273, a mRNA vaccine developed by Moderna, Inc. was the first to enter human trials, with the first volunteer receiving the dose within 10 weeks after SARS-CoV-2 genetic sequencing. The recent interest in mRNA vaccines has been fueled by the state of the art technologies that enhance mRNA stability and improve vaccine delivery. Interestingly, as per the “Draft landscape of COVID-19 candidate vaccines” published by the World Health Organization (WHO) on 12th November, 2020, 6 potential RNA based COVID-19 vaccines are in different stages of clinical trials, of them, 2 are already in Phase III clinical trial. On the other hand, another 22 potential candidates are undergoing preclinical investigations. This review will shed light on the rationality of the RNA as a platform for vaccine development against COVID-19, highlighting the possible pros and cons, lessons learned from the past and the future prospects.